Influence of phototherapy on bond strength and failure modes of enamel bonded to ceramic and metallic brackets with different surface treatment regimes - Almoammar, Salem (Photodiagnosis and photodynamic therapy, 2019)
•Samples treated with total-etch + rinse bonded to metallic and ceramic bracket exhibited comparable bond strength to surface treated with Er, Cr: YSGG phototherapy.•The maximum shear bond strength values were displayed by group 1 surface treated with total etch+rinse bonded to metallic bracket.•The minimum shear bond strength values were exhibited by group 6 surface conditioned with self-etching primers bonded to ceramic bracket.•According to Adhesive Remnant Index lased treated samples yielded admixed failure. The aim of the current study was to assess efficacy of phototherapy on mode of failure and shear bond strength among different brackets in combination with dissimilar conditioning regimens on enamel surface. Ninety maxillary premolars were arbitrarily assigned into six groups (n = 15 each) based on surface conditioning of enamel. Group 1 and group 2 surface treated with total etch + rinse. Group 3 and group 4 surface conditioned with Er,Cr:YSGG. Group 5 and group 6 surface treated with self-etching primer (SEP). Now based on the type of bracket bonded to enamel surface. Group 1, 3 and 5 were bonded to metallic brackets (MB). Similarly, group 2,4,6 were bonded to ceramic bracket (CB). All samples from each group were positioned in a in a universal testing machine for shear bond strength testing. Ten samples from each group were used to discover the sites of bond failure using ARI with stereomicroscope. The mean shear bond strength of six groups were compared by analysis of variance (ANOVA) and pairwise comparison between groups were analysed with the Post hoc Tukey test at a significance level of (p < 0.05). The maximum SBS values were displayed by group 1 total etch + rinse MB (14.84 ± 1.78) whereas the minimum shear bond strength values were exhibited by group 6 SEP CB (9.99 ± 0.91). Samples treated with total etch + rinse MB (14.84 ± 1.78) and group 3 Er,Cr:YSGG MB unveiled comparable bond strength (p > 0.05). Similarly, experimental group 2 total etch + rinse CB (12.52 ± 1.28) was found to be comparable to group 4 Er,Cr:YSGG CB (12.14 ± 4.12) (p > 0.05). Enamel etched for bonding bracket with Er,Cr:YSGG phototherapy at (4.5 W and 30 Hz) displayed comparable bond strength to conventional Transbond XT independent on the type of brackets used.